The Effect of Touch Less Spiritual Therapy and Yin Yoga Toward Student’s Perceived Stress During Covid-19 Pandemic - Oda Debora; Sulistyono Sulistyono (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims : The COVID-19 pandemic has brought massive changes in our lives. This change is also experienced by health students. Movement limitation, changes in social interactions, decrease in learning performance, and learning methods changes are just some of the stressors they tackled nowadays. Prolonged stressors will lead to psychological disorders, especially for health students. The purpose of this study was to determine the effect of touchless spiritual therapy and yin yoga on student perceived stress during the Covid 19 pandemic. Design : This research was quantitative study using a quasi experimental post-test design. Methods : The population of this study were all students at STIKes Panti Waluya Malang, a total of 143 people. Based on Slovin formula, 60 samples were obtained which were taken using a simple random sampling technique. Respondents were divided into two groups, namely treatment and control, each group consisted of 30 respondents. The treatment group did modified touchless spiritual therapy and yin yoga five days a week for 6 weeks, while the control group didn’t. After 6 weeks, respondents of the two groups were asked to filled Perceived Stress Scale questionnaire. Data collection was carried out in the range of early November 2021 to late January 2022. The data was then processed with SPSS 26. Results : Mann-Whitney U Test showed a p value <0.05 (0.03). This means that there was an effect of touchless spiritual therapy and yin yoga toward student’s perceived stress. Conclusions : This study showed that during the pandemic, students experienced stress. Both spiritual approach and physical exercise provided through touchless spiritual healing and yin yoga could help students reduced their perceived stress. Further treatment was needed in order to develop our students psychological health so they become a resillient person which prevent them suffered from mental illness during the pandemic.